ESTONIAN PRINTED HERITAGE IN EXILE: THE CENTRE OF ESTONIAN EXILE LITERATURE AT ACADEMIC LIBRARY OF TALLINN UNIVERSITY - VALMAS, ANNE (Knygotyra, 2015)
Academic Library of Tallinn University Rävala Ave 10, 15042 Tallinn, Estonia E-mail: anne.valmas@tlulib.ee For almost a half-century creative works by Estonians abroad were unknown and inaccessible in the homeland. Exile literature was stored away in the special collections departments of libraries. In 1972, it was decided to set up a special collections department at the ESSR Academy of Sciences Library of the time, which from 1974 onwards could be accessed by a limited group of readers on the basis of special permits. The situation changed in 1988–1989, when the use of the special collections was freed of restrictions. From that time on, the collections were rapidly increased due to book donations by the Estonians abroad. As a result of the steady effort of Academic Library of Tallinn University, the collection of expatriate Estonian literature has become the most complete one of its kind in Estonia, containing over 5000 book titles and over 600 journal titles. The collection contains over 31 thousand published items. The databases have been instrumental to reference activities, conducted by the Centre of Estonian Exile Literature. They are regularly used in the day-to-day work and provide information on the content of the collections. The referred databases are available on the web site of Academic Library of Tallinn University. Collections of expatriate Estonian literature are available in the archives of expatriate Estonians throughout the world as well as in Estonian libraries. In the interests of better preservation, microfilms and digital copies are now prepared from newspapers, which are available on the web site of National Library of Estonia.